2016
DOI: 10.18393/ejss.2016.4.299-306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different nitrogen and potassium sources on lettuce (Lactuca sativa L.) yield in a sandy soil

Abstract: Article Info Received : 05.01.2016 Accepted : 18.04.2016 Lettuce plants were grown under sandy soil conditions in the private farm of Ahmed Orabi organization, Cairo Governorate Egypt, between 15 th November 2009 and 15 January 2010. The experiment was conducted to assess the effects of different nitrogen sources, slow release N (urea-formaldehyde) and fast release N (urea) containing fertilizers at the rates of 0, 60, 90 and 120 kg N ha -1 applied alone or combined with potassium sulphate, on lettuce plant y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
3
11
0
1
Order By: Relevance
“…These results in accordance with the findings of Shaheen et al, (2012);El-Mergawi et al, (2014); Zhang et al, (2014) ;Abdelraouf, (2016); Awaad et al, (2016) and Mahlangu et al, (2016).…”
Section: Discussionsupporting
confidence: 92%
“…These results in accordance with the findings of Shaheen et al, (2012);El-Mergawi et al, (2014); Zhang et al, (2014) ;Abdelraouf, (2016); Awaad et al, (2016) and Mahlangu et al, (2016).…”
Section: Discussionsupporting
confidence: 92%
“…For the nitrogen source x nitrogen content interaction, the NitroMais source always corresponded to the highest averages in the characteristics of ALT, DCL and DCA, except only at the concentration of 150 (Table 2). In the work of Awaad et al (2016), the results indicated that the application of slow release nitrogen fertilizer, alone or combined with potassium sulfate, significantly improved the yield and yield quality of lettuce plants cultivated in sandy soil. Quadratic effect was observed in ALT, DCL, DCA, NFC and PFC in the Americana genotype for both nitrogen sources, whereas Crespa genotype showed similar behavior for DCL and DCA in NitroMais and NFC and PFC fertilizer in Polyblen (Figure 1 and Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Application of different sources of N with combination of potassium sulphate increased the EC of the soil above that of soil fertilized with slow release N fertilizer alone. Application of N and potassium sulphate together decreased the pH and the amounts of N and P in the soil, but increased the quantity of potassium, (Awaad et al, 2016).…”
Section: Fig 2 Effects Of Nitrogen Fertilization On Availablementioning
confidence: 92%